Wolnomularstwo a Kościół katolicki w II Rzeczypospolitej. Kontrowersje i polemiki - Waingertner, Przemysław (Acta Universitatis Lodziensis. Folia Historica, 1995)
The relations between freemasonic organisations and the Catholic Church turned out badly since the moment of birth of modern freemasonery in the 18th century. It was caused by Church distrust of the idea of ideological tolerance, preached by freemasons, and the Catholic clergy fear of spreading universal freemasonic ideology which could compete with the clerical one. In interwar Poland the Catholic Church, supported by the national right wing, had hostile attitude towards the lodges. Under the propaganda of the Catholic national camp a negative stereotype of freemasonic organizations was shaped in the 2nd Rzeczpospolita public opinion. Its appearance could not be disturbed by few freemasons’ and liberals’ manifestations defending the lodges. The opponents of freemasonic orders accused them of fighting the Catholic doctrine, the wish to humiliate the institution of the Church, breaking up the Catholics’ unity and the attempts to destroy Christianity. National - Catholic circles saw in freemasonery „Antichurch” - a centre coordinating the work of groups, organizations and movements opposing the Catholic church domination in political and religious life of interwar Poland. In fact, freemasons were not a real threat for the Catholic church in the 2nd Rzeczpospolita. Freemasonic thought was inspired by Christianity and many members of the lodges were believing Christians. Preached by freemasons ideological tolerance assumed full freedom of all religious cults of course a Catholic one included. In interwar Poland there were very few attempts of reliable analysis of the lodges’ attitude towards the Catholic church. The picture which dominated described a freemason as an atheist, an enemy of religion but first of all of Catholicism. Although this picture became very popular it was far from the truth as well.